Study on Carbonyl Emissions of Diesel Engine Fueled with Biodiesel - Ruina Li; Zhong Wang; Guangju Xu (International Journal of Chemical Engineering)
Biodiesel is a kind of high-quality alternative fuel of diesel engine. In this study, biodiesel and biodiesel/diesel blend were used in a single cylinder diesel engine to study the carbonyl emissions. The result shows that carbonyl pollutants of biodiesel and biodiesel/diesel blend are mainly aldehyde and ketone compounds with 1–3 carbon atoms, and formaldehyde concentration is higher than 80% of the total carbonyl pollutants for biodiesel. The formaldehyde concentration peak is reduced with the increase of intake temperature (T), intake pressure (P), and exhaust gas recirculation (EGR) ratio and increased with the increase of compression ratio (ε). When excess air coefficient (λ) is lower than 1.7, the formaldehyde concentration is increased with the increase of excess air ratio. When λ is higher than 1.7, the formaldehyde concentration is reduced with the increase of excess air ratio. The dilution of air can reduce formaldehyde concentration in the premixed flame of diesel effectively; however, it has less effect on biodiesel. Among the fuel pretreatment measures of adding hydrogen, CO, and methane, the addition of hydrogen shows the best effect on reducing formaldehyde of biodiesel.